2021
DOI: 10.1515/tnsci-2020-0164
|View full text |Cite
|
Sign up to set email alerts
|

A new surgical method of treatment spontaneous intracranial hemorrhage

Abstract: Objective This study aimed to determine the safety and effectiveness of DTI-assisted neuroendoscopy for treating intracranial hemorrhage (ICH). Methods This retrospective study included clinical data from 260 patients with spontaneous supratentorial ICH who received neuroendoscopic hematoma removal. Patients were separated into groups based on the surgery method they received: DTI-assisted neuroendoscopy (69 cases) and standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Surely, the technique is open for further improvement, for example a more specific and elaborated planning of the trajectory by using DTI to determine – and thereby sparing –the white matter tracts [as, e.g., reported by Du et al, Steineke and Barbery and Zhang et al ( 44 46 )] and also predict clinical outcome ( 47 , 48 ). Additionally, the supplement of tractography could be used to further evaluate the presence and role of surviving white matter tracts within the hematoma that are thought to be at risk for damage by the surgical intervention ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Surely, the technique is open for further improvement, for example a more specific and elaborated planning of the trajectory by using DTI to determine – and thereby sparing –the white matter tracts [as, e.g., reported by Du et al, Steineke and Barbery and Zhang et al ( 44 46 )] and also predict clinical outcome ( 47 , 48 ). Additionally, the supplement of tractography could be used to further evaluate the presence and role of surviving white matter tracts within the hematoma that are thought to be at risk for damage by the surgical intervention ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of endoscopic hematoma removal have reported a hematoma removal rate of 90.3% (87.0%-90.9%) and a rebleeding rate of 3.3% (2.9%-4.0%). 7,11,12,[26][27][28][29][30][31][32] The surgical results in this study were comparable to those previously reported, and the hematoma stiffness was correlated with these results. As expected, group S had more FHR and shorter endoscopic procedure times than group F. Furthermore, both patients whose endoscopic hematoma removal procedure was abandoned belong to group F. Therefore, hematoma stiffness correlates with the surgical results, and predicting hematoma stiffness during endoscopic surgery may help surgeons determine the appropriate treatment strategies.…”
Section: Discussionunclassified